An unusual presentation and management of incarcerated Richter’s type of Spigelian hernia: a rare case report and review of literature - Ravi, Prabhu; Rajebhosale, Ramprasad; Husain, Najam (International Surgery Journal, 2020)
Spigelian hernias (SH) are one of the rare forms of ventral abdominal hernias which constitutes about 1-2%. SH occurs through the defect in the anterior abdominal wall adjacent to the semilunar line which occurs in the lower abdomen where the posterior sheath is deficient. The usual presentation of SH is a painful mass in mid abdomen above anterior superior iliac spine (ASIS). The diagnosis is made by means of ultrasound and computed tomography (CT). We report 69 years old female who is a known case of Parkinson’s disease and on medication presented with 2 days of sudden-onset right iliac fossa (RIF) associated with intermittent nausea, vomiting and also abdominal distension. O/E: Abdomen soft, tenderness in RIF with swelling above the line of ASIS. With the diagnosis of lateral abdominal wall hernia we took a CT scan that shows obstructed SH. Immediately she underwent surgery, intra-operative picture shows intraparietal hernia with Richter’s type and viable bowel. Abdominal wall is very weak and flimsy with no proper differentiation between the layers. Preperitoneal mesh repair was performed. The post-operative (post op) period was uneventful. Till now there was only 6 type of Richter’s SH reported. In this article we discuss a brief knowledge of SH and the management part of SH. We hope that this article will benefit among the surgeons in treating with SH.